Elektromagnetske strukture temeljene na pasivnim i aktivnim metamaterijalima približno nulte permitivnosti : doktorski rad - Muha, Damir; Hrabar, Silvio (Zagreb, D. Muha ; Fakultet elektrotehnike i računarstva, 2015)
SAŽETAK: Električni nulti metamaterijali su umjetne elektromagnetske strukture s nultom vrijednosti efektivne permitivnosti. Nedavno je u literaturi teorijski predviđena mogućnost smanjenja izmjera lijevak antene uz pomoć nultih metamaterijala. U ovoj tezi je mogućnost minijaturizacije istražena numerički, pomoću punovalnih simulacija i eksperimentalno, konstrukcijom skraćene lijevak antene u 10 GHz mikrovalnom području. Jedan od nedavno predloženih primjena nultih metamaterijala je i u plazmoničkim nano-strukturama u optičkom području. Nažalost, izrada nano-struktura je vrlo skupa i složena. Međutim, nedavno objavljena istraživanja su pokazala da je raspodjela elektromagnetskog polja unutar sfernog žičanog radio-frekvencijskog rezonatora vrlo slična raspodjeli polja u plazmoničkim nano-strukturama u optičkom području. Stoga su projektirane i praktično izvedene radiofrekvencijske replike koje omogućuju ispitivanje elektromagnetskih svojstava nano-kugli pomoću skaliranih eksperimenata u radiofrekvencijskom području do 1 GHz. Nadalje, istražena je uskopojasnost koja je najveći nedostatak svakog pasivnih metamaterijala a uzrokovana je temeljnom fizikom (disperzijskim jednadžbama). Naposljetku, u literaturi su se nedavno pojavile ideje proširenja pojasa pomoću ne-Fosterovih reaktivnih elemenata. Stoga su analizirani, projektirani i praktično izvedeni negativan kapacitet i induktivitet za širokopojasni rad u radiofrekvencijskom području do 800 MHz. Radi povećanja funkcionalnosti, ovim sklopovima je dodana mogućnost promjene vrijednosti negativnog kapaciteta, odnosno induktiviteta, pomoću upravljačkog istosmjernog napona. - KLJUČNE RIJEČI: metamaterijali, antene, plazmoničke nanosfere, ne-Fosterovi elementi
ABSTRACT: Epsilon-near-zero (i.e. ENZ) metamaterials are artificial electromagnetic structures with approximately zero-valued permittivity. An interesting idea of a reduced length horn antenna, obtained by embedding double wire medium inside it, has been introduced recently. It is well known that the maximal gain of the horn antenna is constrained with the maximal length by which the excessive phase variations of the wave front across the aperture are avioded . Thus, it is clear that an empty shorted horn would possess inherently lower gain compared to the one with optimal dimensions due to pronounced phase variation caused by the spherical wave front. However, the results of numerical simulations performed throughout this thesis showed that embedding of the double wire medium within the shortened horn yields gain equal to the gain of the optimal horn (although within the narrow frequency range). The proposed design on the first sight appears to be similar to an ancient design of horn antennas with artificial dielectric lens. However, it should be noted that the operation principles of the two mentioned shorted horn designs are slightly different. The input and the output surfaces of the slab made out of double-wire medium are parallel so the phase shift introduced by the propagation of the wave within the slab is negligible (due to very small permittivity). Thus the slab cannot make the wave front straight by introducing different phase shifts for different rays. This means that strictly speaking, the wire medium slab does not exhibit the same properties as conventional lens. In this thesis we also report an experimental verification of this idea by development of six shortened horn antennas that operate at the frequency around 10 GHz, which is followed by development of the horn with embedded single-wire ENZ slab and the horn with embedded double-wire ENZ slab. These horn antennas possess lengths of 52% and 33% of the length of the optimal horn, respectively. The measured gain was found to be very similar to the gain of the full length optimal horn (within 0.1 dB), although in a narrower band (5% - 12%) compared to optimal horn. This means we have obtained an increase in gain of almost 7 dB compared to the bare shorted horn, as well as a main lobe width of 16 degrees. Alongside the experimental design, we present numerical results by which it was found that a Drude dispersion model can be deemed as a good starting point for the initial design of a shortened horn, while the required antenna characteristics can afterwards achieved by an additional numerical optimization. In the next part of the thesis we explore so-called plasmonic nano-structures, which is another recently proposed application of epsilon-near-zero metamaterials. Namely, there is a considerable interest in possible use of plasmonic nanospheres made out of the noble metals (such as silver) as building blocks of the future optical waveguides and metamaterials. It was already shown by other authors that it is possible to guide the electromagnetic energy along a chain of the plasmonic nanospheres. Furthermore, it was theoretically predicted that several 1D chains of plasmonic nanospheres would support backward waves, which in turn can be used for construction of optical metamaterials with negative index of refraction. Unfortunately, any experimental investigation of these ideas is extremely difficult and expensive in the optical regime at the present state of the art. To overcome these limitations, in this thesis we work on the idea of the scaled experiments in the RF regime, based on the arrangements of spherical resonators that behave as the ‘RF replicas’ of plasmonic nanospheres. It was shown both theoretically and experimentally that so-called Best’s spherical resonator behaves as the RF replica of plasmonic sphere. The chain of these RF replicas was subsequently manufactured and successfully used for the experimental investigation of nanophotonic devices and optical metamaterials by the scaled experiments in RF regime. Both numerical and experimental investigation showed that the distribution of the electric field inside the sphere is similar to the distribution in the sphere filled with continuous anisotropic ENG material described by Lorentz dispersion model. The experiemntally determined phase distribution of the electric field inside the sphere was found to be opposite to the phase distribution outside the sphere poles. Additionally, the existence of the forward and backward waves on the experimental chain was confirmed - in the case of the transverse polarization, backward-wave propagation was observed, while in the case of longitudinal polarization, forward-wave propagation was observed. Using the full-wave numerical simulations it was also confirmed that it is feasible to construct a scaled experiments in RF regime that mimic behaviour of collections of plasmonic spheres at optical frequencies. The obtained results revealed two main features of an arrangement of plasmonic spheres which are theoretically predicted in recent literature; a circulating displacement current and the occurrence of negative magnetic polarizability (i.e. negative permeability). In the final part of the thesis, an attempt to overcome an inherent narrow-band operation of every passive metamaterial caused by basic physics (i.e. dispersion equation) is proposed. The basis for overcoming such drawback is the inclusion of non-Foster elements which has recently been proposed in literature. In particular, novel negative capacitors and inductors have been analysed, designed and manufactured, which are intended for use in broadband active metamaterial operating in radiofrequency regime (from 10 kHz up to 800 MHz). Closely related with the realization of the proposed elements, negative serial RLC resonant circuit has been analysed theoretically and experimentally. The derivation of reactance of that circuit is found to be negative, which is opposite to normal serial RLC resonator, i.e. negative RLC circuit is non-Foster element. Furthermore, numerical and experimental analysis of segment of transmission line loaded with serial connection of negative non-Foster capacitor and negative non-Foster resistor was performed. In the final stage, the feature that enables tuning of negative capacitance and inductance by the DC control voltage has been implemented in order to increase the versatility of these circuits. - KEYWORDS: metamaterials, antenna, plasmonic nanospheres, non-Foster elements
Na spor. nasl. str. naslov na eng. jeziku: Electromagnetic structures based on passive and active epsilon-near-zero metamaterials : doctoral thesis
Bibliografija: listovi 159-164. - Sažetak na eng. i hrv. jeziku. - Životopis [uključuje i popis objavljenih radova autora]